Low Vision Services in the Asia-Pacific Region: Models of Low Vision Service Delivery and Barriers to Access. (July 2014) - Lim, Yong Ern; Vukicevic, Meri; Koklanis, Konstandina; Boyle, Jessica
The aim of this discussion paper is to provide a general overview of the different models of low vision service provision in the Asia-Pacific region. In addition, the significant global barriers hindering patient access to low vision services will be highlighted.